2000
DOI: 10.1044/jslhr.4302.548
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Length and Syntactic Complexity on the Speech Motor Stability of the Fluent Speech of Adults Who Stutter

Abstract: The purpose of the present study was to investigate the impact of utterance length and syntactic complexity on the speech motor stability of adults who stutter. Lower lip movement was recorded from 8 adults who stutter and 8 normally fluent controls. They produced a target phrase in isolation (baseline condition) and the same phrase embedded in utterances of increased length and/or increased syntactic complexity. The spatiotemporal index (STI) was used to quantify the stability of lower lip movements across mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
134
10
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(162 citation statements)
references
References 20 publications
16
134
10
2
Order By: Relevance
“…Regarding speech RT, the data of this study agrees with the findings of Bosshardt et al 13 who found no differences between suttering and fluent individuals and with the data of Kleinow and Smith 14 who found a greater variability in the temporal patterns of stuttering individuals (in the present study the group of stutterers presented results four times more disperse than their controls). This variability, indicated by the dispersion of the data, suggests that the speech system of stuttering individuals requires several attempts prior to speech in order to reach a fluent pattern.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Regarding speech RT, the data of this study agrees with the findings of Bosshardt et al 13 who found no differences between suttering and fluent individuals and with the data of Kleinow and Smith 14 who found a greater variability in the temporal patterns of stuttering individuals (in the present study the group of stutterers presented results four times more disperse than their controls). This variability, indicated by the dispersion of the data, suggests that the speech system of stuttering individuals requires several attempts prior to speech in order to reach a fluent pattern.…”
Section: Discussionsupporting
confidence: 82%
“…Several authors point that high muscle activity makes speech more vulnerable to disruptions 1,3,6,14,15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, studies of stuttering speakers' motor execution showed aberrant coordination among articulatory, laryngeal, and respiratory systems during both stuttered and fluent speech (e.g., Loucks and De Nil, 2006;Loucks et al, 2007;Max et al, 2003;Namasivayam and van Lieshout, 2008). Second, studies of linguistic factors related to the speech planning process revealed altered semantic, syntactic, and especially phonological processing in both child and adult stuttering speakers, even in the absence of any speech production requirements (e.g., Cuadrado and Weber-Fox, 2003;Kleinow and Smith, 2000;Ratner and Sih, 1987;Sasisekaran et al, 2006;Weber-Fox, 2001;Weber-Fox et al, 2004). Finally, there is also evidence indicating an atypical interface between planning and execution processes (e.g., Blomgren and Goberman, 2008;Dworzynski et al, 2004;Savage and Howell, 2008;Snyder et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas specific information regarding underlying motoric processes cannot be inferred from surface analyses of disfluent speech (Kent, 1996;Kleinow & Smith, 2000;van Lieshout, Hulstijn, & Peters, 2004), the theory of coordination dynamics could provide one explanation for the variability in the two speech samples. Control of motor systems, according to this theory, is achieved through coupling, for example, between articulators (Kelso, 1995).…”
Section: Articulation Ratementioning
confidence: 99%